Insulin Resistance in Children - Tagi, Veronica Maria; Giannini, Cosimo; Chiarelli, Francesco (Frontiers in Endocrinology, 2019)
Insulin resistance (IR) is a pathological condition strongly associated with obesity. However, corticosteroids or growth hormone therapy and genetic diseases may affect insulin sensitivity lifelong. In obese children and adolescents of any age there is an evident association between IR and an increased prevalence of type 2 diabetes (T2D) and other elements contributing to the metabolic syndrome, leading to a higher cardiovascular risk. Therefore, early diagnosis and interventions in the attempt to prevent T2D when glycemia values are still normal is fundamental. The gold standard technique used to evaluate IR is the hyperinsulinemic euglycemic clamp, however it is costly and difficult to perform in clinical and research sets. Therefore, several surrogate markers have been proposed. Although the treatment of insulin resistance in children is firstly targeted to lifestyle interventions, in selected cases the integration of a pharmacological intervention might be taken into consideration. The aim of this review is to present the current knowledge on IR in children, starting with an outline of the recent evidences about the congenital forms of deficiency in insulin functioning and therefore focusing on the physiopathology of IR, its appropriate measurement, consequences, treatment options and prevention strategies.